The economics and finance of commodity price shocks - Mohammed, Mikidadu (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"The behaviour of commodity prices never ceases to marvel economists, financial analysts, industry experts, and policymakers. Unexpected swings in commodity prices used to occur infrequently but have now become a permanent feature of global commodity markets. This book is about modelling commodity price shocks. It is intended to provide insights into the theoretical, conceptual, and empirical modelling of the underlying causes of global commodity price shocks. Three main objectives motivated the writing of this book. First, to provide a variety of modelling frameworks for documenting the frequency and intensity of commodity price shocks. Second, to evaluate existing approaches used for forecasting large movements in future commodity prices. Third, to cover a wide range and aspects of global commodities including currencies, rare-hard-lustrous transition metals, agricultural, energy, and health pandemics. Some attempts have already been made towards modelling commodity price shocks. However, most tend to narrowly focus on a subset of commodity markets, i.e., agricultural commodities market and/or energy market. In this book, the author moves the needle forward by operationalizing different models, which allow researchers to identify the underlying causes and effects of commodity price shocks. Readers also learn about different commodity price forecasting models. The author presents the topics to readers assuming less prior or specialist knowledge. Thus, the book is accessible to industry analysts, researchers, undergraduate and graduate students in economics and financial economics, academic and professional economists, investors, and financial professionals working in different sectors of the commodity markets. Another advantage of the book's approach is that readers are not only exposed to several innovative modelling techniques to add to their modelling toolbox but are also exposed to diverse empirical applications of the techniques presented"--
Keywords: Prices -- Econometric models; Supply and demand -- Econometric models; BUSINESS & ECONOMICS / Economics / Macroeconomics; BUSINESS & ECONOMICS / Econometrics; BUSINESS & ECONOMICS / Economic Conditions